Millennialism, rapture and "Left Behind" literature. : Analysing a major cultural phenomenon in recent times - De Villiers, Pieter GR (Stellenbosch Theological Journal, 2020)
This article represents a research overview of the nature, historical roots, social contexts and growth of millennialism as a remarkable religious and cultural phenomenon in modern times. It firstly investigates the notions of eschatology, millennialism and rapture that characterize millennialism. It then analyses how and why millennialism that seems to have been a marginal phenomenon, became prominent in the United States through the evangelistic activities of Darby, initially an unknown pastor of a minuscule faith community from England and later a household name in the global religious discourse. It analyses how millennialism grew to play a key role in the religious, social and political discourse of the twentieth century. It finally analyses how Darby's ideas are illuminated when they are placed within the context of modern England in the sixteenth, seventeenth and eighteenth century. In a conclusion some key challenges of the place and role of millennialism as a movement that reasserts itself continuously, are spelled out in the light of this history.